The politics of housing : power, consumers and urban culture (MANCHESTER UNIV Press, 2007)
Exploring the politics of housing from 1890-1990, this fascinating study examines the interaction not only of national and local politics but also of local factors such as civic culture, key local players, local discourse and geographical and demographic problems. This book argues that increasingly, tenants acted as consumers of a public service, and it questions the way in which notions of consumerism shaped responses to the housing debate. An analysis of the impact of legislation on housing policy in different cities is provided, as well as a more detailed account of the politics of housing.